Explanatory and Confirmatory Holistic Services Based on the Synoptic Gospels Among Children PPA Ages 14-19 Years Old Cluster Solo - Matius I Totok Dwikoryanto; Muner Daliman; Hana Suparti; Paulus Sentot Purwoko (Jurnal Teologi (JUTEOLOG), 2022)
A growing church is a church that prioritizes the ministry of children, because children are the next generation of the church. However, there are indications that there are still churches that do not view children's services as important and make them a priority for programs, funding, facilities and infrastructure. Service priority is more for adult services, compared to child services. This indicates that the church does not understand Holistic Ministry based on the Synoptic Gospels. Children's ministry is a very important service and requires adequate human resources support, both in terms of quantity and quality. In fact, there are indications that the Church still suffers from a lack of quality human resources, both in terms of calling and quality in carrying out child services, weak basic vocations, PPA human resources do not understand the development of the current situation so that the approach to fostering children is not appropriate. From the various problems that the researcher described above, the researcher believes that apart from these problems, the background factors of PPA children aged 14-19 years have a role in the implementation of Child Holistic Services based on the Synoptic Gospels. These backgrounds include: educational age background, economy, ethnicity, and length of time participating in PPA. For this reason, the researcher wrote a dissertation entitled: "Explanatory and Confirmatory Holistic Services based on the Synoptic Gospels among PPA Children aged 14-19 years in the Solo Cluster" to obtain empirical data from these problems and produce implications and suggestions for the development of PPA in the Solo Cluster.